AB0536 Tocilizumab offers clinical and ultrasonographic improvement in rheumatoid arthritis patients. Results of a 6 months follow-up study. (23rd January 2014) - Bouaddi, I.; Rkain, H.; Aktaou, S.; Raissouni, H.; Traki, L.; Bouazzaoui, L.; Benchakroun, B.; Benbrahim, L.; Rostom, S.; Allali, F.; Bahiri, R.; Amine, B.; et al.
Abstract : Background: Tocilizumab (TCZ) is a humanized anti-interleukin 6 (anti-IL 6) receptor antibody that has been demonstrated in previous clinical trials to improve rheumatoid arthritis (RA) and prevent radiographic progression. Musculoskeletal ultrasonography (MSUS) has increasingly been used as outcome measures in clinical trials of RA. Thus, we aimed to evaluate clinical and ultrasonographic (US) progression in RA patients treated with TCZ. Methods: Twenty two consecutive patients, affected by RA [19 females, median age of 41 years (35, 50), median disease duration of 72 months (36, 171)] who were non-responders or partial responders to DMARDs therapy were commenced on Tocilizumab. The patients underwent clinical, laboratory, and assessment at baseline and after 6 months. The Disease Activity Score in 28 joints (DAS28) was recorded at inclusion and after a 6 months of therapy.The German ultrasound score included the following joints of the clinically dominant hand and foot: wrist, second and third metacarpophalangeal and proximal interphalangeal, and second and fifth metatarsophalangeal joints. Synovitis and synovial vascularity were scored semiquantitatively (grade 0–3) by gray-scale (GS) and power Doppler (PD) ultrasound. Clinical remission after 6 months of treatment was defined when DAS 28 was <2.6. Results: At baseline, the median DAS28 score was 5.2 (4.4, 6.2) and the synovitis scores were 9.5 (6.7, 15) in GS ultrasound and 2.5 (0, 7.2) in PD ultrasound. After 6 months of therapy, the DAS28 significantly decreased to 1.6 (0.8, 2.4); p<0.001 and the GS and PD ultrasound scores significantly decreased to respectively 5 (4, 6); p=0.001 and to 0.5 (0, 1.7); p=0.04. Remission at 6 months was noted in 70% of patients. Conclusions: This study indicates good evolution of RA patients under TCZ on basis on clinical and ultrasonographic findings. These results should be verified by further studies. Disclosure of Interest: None Declared